Correlation of central corneal thickness and axial length to the optic disc and peripapillary atrophy among healthy individuals, glaucoma and ocular hypertension patients - Michalis Moschos (Dove Medical Press, 2008)
George Tomais1, Gerasimos Georgopoulos2, Chryssanthi Koutsandrea2, Michalis Moschos21University of Athens, Department of Ophthalmology, Athens, Greece; 2Athens University Medical School, Department of Ophthalmology, Athens, GreecePurpose: Clinical observational study for the correlation between the central corneal thickness (CCT), axial length (AXL), optic disc area (D), cupping area (C) and peripapillary atrophy (PPA), in healthy eyes (group A), eyes with primary open angle glaucoma (POAG) (group B) and eyes with ocular hypertension (OH) (group C), in order to assess the possible contribution of this correlation to the diagnosis or prognosis of glaucoma.Methods: Ninety eyes of 90 persons participated in the study (30 eyes of 30 persons in each group). All eyes underwent intraocular pressure measurement, visual field testing, endothelial cell count (ECC), measurement of the CCT and AXL, and gonioscopy. After dilation of the pupil, a digital photograph of each optic disc was performed, followed by PPA, D area and C area measurements.Results: We found a statistically significant difference in the C/D area ratio between healthy and POAG eyes and a moderate negative relationship between AXL and D in healthy eyes. We also found a moderate negative relationship between CCT and C/D area ratio in POAG eyes and a strong negative relationship between PPA and D in OH eyes.Conclusions: CCT was not correlated with PPA and AXL in any one of the three groups. OH eyes seem to have more tolerant and stable disc and peripapillary area compared to healthy and POAG eyes.Keywords: glaucoma, peripapillary, cupping, corneal thickness, axial length, optic disc